OVO: o hibridismo no design brasileiro contemporâneo - Gomes, Rogério Zanetti; Pinheiro, Olimpio José [UNESP] (My University, 2010)
The present study, is characterized as qualitative investigative, has as main objective to analyze the convergence between the fields of the visual arts and design. To base the analysis, it was developed a bibliographical research that raised the concept of hybrid language, the mixing of different races in Brazilian design, the relations between art and design and the Design Prize Museum of Brazilian House (MCB). As shown on the basis of this theoretical survey, it was presented the designers Luciana Martins and Gerson de Oliveira, from the company, OVO, and the objects selected for this study, that are the two products awarded from the MCB, which contain artistic characteristics and are commercialized and recognized as objects of Brazilian design. These products were analyzed and the hybrid characteristics of them were raised.

O presente estudo, que se caracteriza investigativo qualitativo, tem como objetivo principal analisar a convergência entre os campos das artes visuais e do design. Para fundamentar a análise, foi desenvolvida uma pesquisa bibliográfica que levantou o conceito de linguagem híbrida, a mestiçagem no design brasileiro, as relações entre arte e design e o Prêmio Design Museu da Casa Brasileira (MCB). Com base nesse levantamento teórico, foram apresentados os designers Luciana Martins e Gerson de Oliveira, da empresa ,OVO, e os objetos selecionados por este estudo, que são os dois produtos premiados pelo MCB, que possuem características artísticas e são comercializados e reconhecidos objetos do design brasileiro. Esses produtos foram analisados e foram levantadas as características híbridas dos mesmos.
Keywords: Design; Visual arts; Hybridism; OVO; Design; Artes visuais; Hibridismo; OVO